If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7c + -77 = 4c + -35 Reorder the terms: -77 + 7c = 4c + -35 Reorder the terms: -77 + 7c = -35 + 4c Solving -77 + 7c = -35 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. -77 + 7c + -4c = -35 + 4c + -4c Combine like terms: 7c + -4c = 3c -77 + 3c = -35 + 4c + -4c Combine like terms: 4c + -4c = 0 -77 + 3c = -35 + 0 -77 + 3c = -35 Add '77' to each side of the equation. -77 + 77 + 3c = -35 + 77 Combine like terms: -77 + 77 = 0 0 + 3c = -35 + 77 3c = -35 + 77 Combine like terms: -35 + 77 = 42 3c = 42 Divide each side by '3'. c = 14 Simplifying c = 14
| -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q | | 3+3(2-6)= | | -5+6x=x+10 | | 2s-48=s | | 2s+40=4s+28 | | x/3-=11 | | 3y=7x-9 | | 9x-12y+6=0 | | 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 |